The Orphan Tsunami of 1700 : Japanese Clues to a Parent Earthquake in North America - Atwater, Brian F. (Book collections on Project MUSE., 2015)
From the traces of a devastating tsunami in Japan during the winter of 1700, scientists discover how it was recorded in Japanese history and then backtrack it to its origins via geological evidence in North America. Their work shows how tsunami research has evolved over three centuries and how this event impacts current warning systems.